Mengoptimalkan Program SEHATI: Pendampingan Pelaku UMKM untuk Sertifikasi Halal di Desa Murtajih, Kabupaten Pamekasan - Munawaroh, Siti Ikmatul; Salama, Amanda Ummi; Faizah, Fajrini; Muslim, Hasan Faqih; Ahmad Makhtum (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This service activity program aims to assist Micro and Small Enterprises (UMK) actors in Murtajih Village, Pademawu District, Pamekasan Regency through the Free Halal Certification Program (SEHATI). The methods used in this mentoring activity are preparation, surveys, mentoring through education, and direction. This assistance is carried out to be able to train and accompany business actors so that they can fill out the Si Halal application and input production data into the Si Halal application, as well as carry out verification and validation on products registered in the SEHATI program. The result of this service activity is the existence of halal-certified products for micro- and small-business actors in Murtajih Village through SEHATI submissions in the halal account so that the government program regarding mandatory halal certification regulations can be realized.